The Designing of Illustration Book for River Preservational for Children - Taufik Hendra Lukmana; Patra Aditia (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2014)
The design project of this illustration book is backgrounded by pollutioned river phenomenon which is happening in Bandung, West Java, Indonesia. The pollution is mainly caused by the people behavior which are likely don't care about nature and neither have insight on what matters on it. This river pollution is reach at endangered level and can lead into health and social problem and affect on the environmental aesthetic as well. From that reasons above, education on people is needed to prevent the river from further destruction, recover its cleanness, everlast, and function on ecosystem balance.Target audience of this book is primary school children, who are mainly from family, live on the banks of the river. Children age was chosen because at this age they can rapidly absorb information around them. They also start to pre-change on their attitude, value, and behavior so it is expected to have impact on shaping their care-attitude toward environment at their current or future stage of life. This design project took sample on Cikapundung River located in Bandung Regency, West Java, Indonesia.The outcome of this design project is a picture-story book as an educational media, containing story about characters with implied moral messages. Scene fragments in time and ambience background story came with illustrations and narrations, purpose to communicate the education message. By that message, the target audiences are expected to emerge their attitude and changing behavior toward cleanness and everlast river environment arround them.